AMERICAN VS BRITISH SPELLING PREFERENCES IN SPOKEN TOURISM ENGLISH BY EFL LEARNERS - Yunianti, Eka Pratiwi; Bungsudi, Bungsudi (English Community Journal, 2025)
The issue of spelling variation between British English (BrE) and American English (AmE) in English- language tourism communication is often overlooked in English for Specific Purposes (ESP) instruction, particularly among learners of English as a Foreign Language (EFL). In reality, such variations can significantly influence how professionalism and message clarity are perceived in global communication contexts. This study aims to explore the spelling preferences used in spoken tourism English among two EFL learners, employing a qualitative case study approach. The research subjects were two fifth-semester students from Universitas Aisyah Pringsewu which were selected using purposive sampling. Data were gathered through transcripts of role-play simulations and reflective interviews, and analyzed using thematic coding and a linguistic observation rubric. The findings reveal that both participants predominantly used AmE spelling, influenced more by exposure to digital media than by systematic linguistic awareness. Nevertheless, BrE forms still emerged, particularly in contexts perceived as formal or institutional. These results highlight a limited metalinguistic awareness of spelling variation, which contributes to inconsistent register use in professional tourism communication. Therefore, it is recommended that English language instruction for tourism explicitly incorporate training on spelling variation and contextual usage to foster communicative competence that is both professional and adaptable in international settings.